Respuesta :

Answer:

Simplifying the equation:

[tex]\frac{2}{3} x - \frac{5}{6} = -\frac{5}{12} x + \frac{1}{4}[/tex]

Grouping like terms:

[tex]\frac{2}{3} x + \frac{5}{12} x= \frac{1}{4} + \frac{5}{6}[/tex]

⇒ [tex]\frac{39}{36} x=\frac{26}{24}[/tex]

Solving for 'x', we have:

⇒ [tex]x=\frac{26}{24}\frac{36}{39}=1[/tex]

For this case we place the terms with "x" on the left side of the equation, and the terms without "x" on the right side:

[tex]\frac {2} {3} x + \frac {5} {12} x = \frac {1} {4} + \frac {5} {6}[/tex]

We add similar terms:

[tex]\frac {24 + 15} {36} x = \frac {6 + 20} {24}\\\frac {39} {36} x = \frac {26} {24}[/tex]

We simplify both sides:

[tex]\frac {13} {12} x = \frac {13} {12}[/tex]

Dividing by [tex]\frac {13} {12}[/tex] on both sides of the equation:[tex]x = 1[/tex]

Answer:

[tex]x = 1[/tex]

ACCESS MORE